Welding Numerical Simulation Analysis of AP 1000 Insert Plate and Penetration Sleeves Based on ABAQUS. Issue 1 (1st December 2022) - Yang, Xiaoyu; Guo, Qi; Tang, Shengming; Zhang, Lijun; Chen, Xiaohu; Shi, Xiumei
Abstract : Frequently, cracks are found in welded joints of the insert plate assembly of a nuclear reactor containment vessel. To study the residual stress state of the dissimilar steel welded joint of the insert plate assembly and ensure that there are no defects after welding, the ABAQUS finite element analysis software was used to simulate the temperature field and the post-weld residual stress field of the dissimilar steel inserted into the plate assembly in the containment of the nuclear reactor. The insert plate and sleeve material are SA738GR.B and A350, respectively; the heat treatment process after welding is simulated to predict the residual stress state of the welded joint after heat treatment. The simulation results show that the weld zone is the most sensitive to the circumferential cracks, and the maximum residual stress appears near the weld toe near the tube side.